Early Childhood Education and Care: Special Issue Introduction - Linda Houser; Jessica M. Kahn; Corey S. Shdaimah (Social Work and Society)
This introduction to the special issue addresses early childhood education and care (ECEC) through a social work lens.  Specifically, the introduction highlights how the articles in the special issue draw from social work values, such as social justice, equality, and self-determination.  Together, the articles elucidate the value of using a holistic, person-in-environment orientation to analyze and develop the many aspects of early education and care.  The articles also explore the ways that ECEC work tends to be essentialized, naturalized, and gendered, despite the fact that such work requires skill and has, as its focus, the well-being of future generations.  This introduction and these articles demonstrate the need for advocacy from social workers and our allies to find common ground to improve the systems and daily operations of early education and child care.  Social workers have a role in ECEC research, policy development, and administration, and this introduction and the subsequent articles show how.